Conquerors' road - White, Osmar, 1909-1991. (Cambridge, UK ; Port Melbourne, Vic. : Cambridge University Press, 2003)
"This book by one of Australia's finest chroniclers of the Second World War tells the devastating story of war from the inside. Based largely on the author's own war diary and the articles he wrote as a war correspondent, this deeply personal account is unparalleled amongst the vast literature on World War Two." "Osmar White was there to record and assess the climactic events of that time. He was present at the official German surrender. He was there when the horror of Buchenwald was opened to the world. He saw some of the atrocities visited upon the German people by their Russian conquerors. And he was able to offer those who read his despatches something futher - with insight and compassion he attempted to weigh the moral issues thrown up by victory and by what came after, while trying also to draw lessons for a future humanity. Ultimately, White would speculate that Nazism might find a home "in almost any country in the world" where the conditions were ripe."--BOOK JACKET.
Machine derived contents note: Part I. The Winter Offensive -- Part II. Springtime in Germany -- Part III. Inside Hitler's Reich -- Part IV. The Aftermath -- Part V. Questions and Reflections.
Cover subtitle, "an eyewitness report of Germany 1945".
Reprinting of: Pymble, N.S.W. : HarperPerennial, 1996.
Includes bibliographical references and index.
Keywords: White, Osmar, -- 1909-1991.; United States. -- Army. -- Army, 3rd.; War correspondents -- Australia -- Biography; World War, 1939-1945 -- Personal narratives, Australian; World War, 1939-1945 -- Campaigns -- Germany; World War, 1939-1945 -- Journalism; Germany -- History -- 1945-1955.; Armies; Germany; History, 1901-1945; Overseas item; United States; World War 2